2009
DOI: 10.1111/j.1439-0531.2008.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Meloxicam Treatment during Early Pregnancy in Holstein Heifers

Abstract: We previously reported that administration of flunixin meglumine two times at a critical stage approaching pregnancy recognition associated with maintenance of the corpus luteum (CL) increased early embryo survival and pregnancy rate via an additive antiluteolytic effect with the conceptus [Vet Rec 160 (2007) 404]. In this study, the objective was to determine if a single administration of meloxicam, a non-steroid anti-inflammatory drug with a longer half-life, could be used instead of flunixin meglumine. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 30 publications
1
34
1
1
Order By: Relevance
“…Of note, the expression of PTGS2 in biopsies of day 7 bovine blastocysts is a predictor of the successful development of that blastocyst to term and delivery of a live calf (El-Sayed et al 2006 ). Further, pregnancy rates were substantially reduced in heifers that received meloxicam, a partially selective inhibitor of PTGS2, on day 15 after insemination (Erdem and Guzeloglu 2010 ). A recent study supports the hypothesis that the day 13 conceptus secretes PGs that act locally in a paracrine manner to alter gene expression in the endometrium prior to pregnancy recognition in cattle ).…”
Section: Prostaglandins and Conceptus Elongationmentioning
confidence: 97%
“…Of note, the expression of PTGS2 in biopsies of day 7 bovine blastocysts is a predictor of the successful development of that blastocyst to term and delivery of a live calf (El-Sayed et al 2006 ). Further, pregnancy rates were substantially reduced in heifers that received meloxicam, a partially selective inhibitor of PTGS2, on day 15 after insemination (Erdem and Guzeloglu 2010 ). A recent study supports the hypothesis that the day 13 conceptus secretes PGs that act locally in a paracrine manner to alter gene expression in the endometrium prior to pregnancy recognition in cattle ).…”
Section: Prostaglandins and Conceptus Elongationmentioning
confidence: 97%
“…also be converted into eicosadienoic acid rather than arachidonic acid as reported herein, which is known to reduce PGF 2α synthesis (Staples et al, 1998;Cheng et al, 2001). In addition, recent research demonstrated that PG from the 2-series, such as PGE 2 and PGI 2 that are also originated from ω-6 FA (Schmitz and Ecker, 2008), are critical regulators of conceptus elongation and pregnancy establishment in sheep (Dorniak et al, 2011) and cattle (Erdem and Guzeloglu, 2010). More specifically, these PG are synthesized by the conceptus and endometrium, modulate synthesis and endometrial activity of IFNt, and appear to be fundamental for conceptus development and pregnancy signaling to maternal tissues (Erdem and Guzeloglu, 2010;Dorniak et al, 2011).…”
Section: Plasma and Tissue Fatty Acid Concentrationsmentioning
confidence: 99%
“…Thus, available results support the idea that PG and IFNT from the conceptus coordinately regulate endometrial functions important for growth and development of the conceptus during the periimplantation period of pregnancy. In fact, pregnancy rates were substantially reduced in heifers that received meloxicam, a partially selective inhibitor of PTGS2, on d 15 after insemination (Erdem and Guzeloglu, 2010). Thus, PG are critical regulators of conceptus elongation and implantation, as they are for blastocyst implantation and decidualization during pregnancy in mice, rats, hamsters, mink and likely humans (Dey et al, 2004;Wang and Dey, 2006;Kennedy et al, 2007).…”
Section: Prostaglandins and Cortisol: Potential Mediators Of Progestementioning
confidence: 99%